2014
DOI: 10.1371/journal.pone.0087547
|View full text |Cite|
|
Sign up to set email alerts
|

Embryonic Caffeine Exposure Acts via A1 Adenosine Receptors to Alter Adult Cardiac Function and DNA Methylation in Mice

Abstract: Evidence indicates that disruption of normal prenatal development influences an individual's risk of developing obesity and cardiovascular disease as an adult. Thus, understanding how in utero exposure to chemical agents leads to increased susceptibility to adult diseases is a critical health related issue. Our aim was to determine whether adenosine A1 receptors (A1ARs) mediate the long-term effects of in utero caffeine exposure on cardiac function and whether these long-term effects are the result of changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 56 publications
(72 reference statements)
2
35
1
3
Order By: Relevance
“…An accompanying editorial expressed concern that 'We must now heed the wake-up call sounded by Silva et al (2013) that exposure to psychoactive substances, even a seemingly innocuous, socially well-integrated substance like caffeine, before or soon after birth can alter brain development' (Kabir et al, 2013). Another team has suggested that embryonic caffeine exposure produces an increase in body weight (B10%), alters cardiac function and morphology, and produces long-lasting alterations in DNA methylation (Buscariollo et al, 2014). A third group has focused on the neuroendocrine consequences and found that prenatal caffeine ingestion induces an increased susceptibility to metabolic syndrome with alterations of glucose and lipid metabolic phenotypes that then propagate transgenerationally (Katayama et al, 1987;Xu et al, 2012a;Xu et al, 2012b).…”
Section: Caffeinementioning
confidence: 99%
“…An accompanying editorial expressed concern that 'We must now heed the wake-up call sounded by Silva et al (2013) that exposure to psychoactive substances, even a seemingly innocuous, socially well-integrated substance like caffeine, before or soon after birth can alter brain development' (Kabir et al, 2013). Another team has suggested that embryonic caffeine exposure produces an increase in body weight (B10%), alters cardiac function and morphology, and produces long-lasting alterations in DNA methylation (Buscariollo et al, 2014). A third group has focused on the neuroendocrine consequences and found that prenatal caffeine ingestion induces an increased susceptibility to metabolic syndrome with alterations of glucose and lipid metabolic phenotypes that then propagate transgenerationally (Katayama et al, 1987;Xu et al, 2012a;Xu et al, 2012b).…”
Section: Caffeinementioning
confidence: 99%
“…Epigenetic changes not only affect the exposed embryo, but may also affect subsequent generations and contribute to the development of disease, as shown by endocrine disruptors vinclozolin and bisphenol A 14, 15 . Research in our laboratory has demonstrated that in utero caffeine exposure disrupts adenosine action and leads to long-term adverse effects on cardiac function 1618 . Furthermore, depending on the timing of exposure, caffeine has transgenerational effects on cardiac function 16 .…”
Section: Fetal Programming Of Adult Diseasementioning
confidence: 99%
“…Research in our laboratory has demonstrated that in utero caffeine exposure disrupts adenosine action and leads to long-term adverse effects on cardiac function 1618 . Furthermore, depending on the timing of exposure, caffeine has transgenerational effects on cardiac function 16 .…”
Section: Fetal Programming Of Adult Diseasementioning
confidence: 99%
“…Genomic DNA was isolated with the DNeasy Blood & Tissue Kit (Qiagen) and treated with RNase to remove RNA contaminants. The MethylFlash Methylated DNA Quantification Kit (Colorimetric; Epigentek, Farmingdale, NY) and MethylFlash Hydroxymethylated DNA Quantification Kit (Colorimetric; Epigentek) were used to quantitate the percentage of 5mC and 5hmC in genomic DNA samples, respectively (4,16). After colorimetric reaction, the methylated cytosine was measured with a Synergy HT Multi-Mode Microplate Reader (BioTek, Winooski, VT).…”
Section: Materials Nmentioning
confidence: 99%